The role of earnings management as mediator the effect of male CEO masculinity face on Research & Development - Januar Eko Prasetio; Sabihaini; Sudaryanto; Haryati Setyorini; Rusdiyanto; Anisaul Hasanah; Adiba Fuad Syamlan; A. Maya Rupa Anjeli (Cogent Business & Management, 2023)
This study aims to explain the role of earnings management in mediating the influence of male CEO masculinity on research & development. This study uses a quantitative approach with a population and research sample using companies on the Indonesia Stock Exchange in 2017-2021. This study collects facial images identified as male CEOs from data on the Indonesia Stock Exchange website and company websites and utilizes Google search. The data analysis method in this study uses Structural Equation Modeling which links theory, concepts and data that can be applied to research variables using Stata software. The findings explain that the role of earnings management mediates the influence of the male CEO's masculinity face on research &development, meaning that the increase and decrease in the part of earnings management has an impact on increasing and decreasing the masculinity face of male CEOs also has an impact on increasing and decreasing research & development. The practical impact of the research results can help the Indonesian Institute of Accountants develop Financial Accounting Standard No. 19 in Indonesia. Theoretical implications of the research results can explain agency theory and behavioral consistency theory. The findings empirically have implications for company management in making policies related to the face of male masculinity which have an impact on earnings management practice policies and policy making on research & development expenditures, so that the empirical findings can be used by company management and the Indonesian government as policy makers in developing countries as a comparison of developed country policies. Throughout the study's observations to date, it has not found any research on the topic of the role of profit management mediating the influence of the masculinity of male CEOs associated with research & development costs. The distinct role of male CEOs affects research & development policies and cost. The originality of this study can be shown by the differences from previous studies, first (Jia et al., 2014) explain that the face of masculinity of male CEOs has a positive effect on profit management practices. The second (Kamiya et al., 2018a; Asyik et al., 2022) explains that the face of masculinity of male CEOs has a positive impact on leverage. Research & development in the company have an essential position to increase the company's long-term profitability
Keywords: G32; G34; G02; M1; Z1; 650; R&D; SEM; earnings management; CEO male; masculinity; Stata; fWHR